2005
DOI: 10.1001/jama.294.8.903
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia-Assisted vs Buprenorphine- or Clonidine-Assisted Heroin Detoxification and Naltrexone Induction

Abstract: These data do not support the use of general anesthesia for heroin detoxification and rapid opioid antagonist induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 66 publications
3
77
1
2
Order By: Relevance
“…Newer protocols focused on identifying optimal doses and treatment durations of buprenorphine, naltrexone, and clonidine to shorten induction periods, while minimizing the severity of withdrawal. Major changes to earlier protocols involved reducing buprenorphine treatment to 1–2 days, shortening to 1 day the “washout” period before starting naltrexone, and decreasing the first dose of naltrexone from 12.5 to 3 mg, with supportive medications, usually standing doses of clonidine and clonazepam administered at frequent dosing intervals 51, 52, 53, 54, 55, 56, 57. A 2017 study comparing outpatient detoxification regimens showed that an oral naltrexone‐assisted detoxification regimen, compared with a descending buprenorphine taper followed by a 7‐day washout period, was more likely to lead to successful XR‐NTX induction (56% vs. 33%) and a second XR‐NTX dose (50% vs. 27%) 58…”
Section: Historical Perspective On Clinical Management Of Opioid Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer protocols focused on identifying optimal doses and treatment durations of buprenorphine, naltrexone, and clonidine to shorten induction periods, while minimizing the severity of withdrawal. Major changes to earlier protocols involved reducing buprenorphine treatment to 1–2 days, shortening to 1 day the “washout” period before starting naltrexone, and decreasing the first dose of naltrexone from 12.5 to 3 mg, with supportive medications, usually standing doses of clonidine and clonazepam administered at frequent dosing intervals 51, 52, 53, 54, 55, 56, 57. A 2017 study comparing outpatient detoxification regimens showed that an oral naltrexone‐assisted detoxification regimen, compared with a descending buprenorphine taper followed by a 7‐day washout period, was more likely to lead to successful XR‐NTX induction (56% vs. 33%) and a second XR‐NTX dose (50% vs. 27%) 58…”
Section: Historical Perspective On Clinical Management Of Opioid Withmentioning
confidence: 99%
“…Up to one third of patients who receive XR‐NTX use illicit opioids at some point during treatment, commonly as single episodes to “test” the blocking effect of the medication 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 62. A recent study of patients using opioids during XR‐NTX blockade found that most did not feel euphoria and used lower doses than before receiving XR‐NTX.…”
Section: Current Approach To Treatment Of Opioid Use Disorder: Choosimentioning
confidence: 99%
“…Oreskovich [24] in his study reported that suppression of withdrawal was achieved in the first 24 hours of treatment for 50% patients on buprenorphine and in 11% of cases treated with clonidine and COWS scores were significantly less in the buprenorphine group over the day 5 th of treatment. Contrary to most of the studies Collins [25] and Umbricht., [26] reported no significant difference in withdrawal severity for groups treated with buprenorphine, compared to those treated with clonidine.…”
Section: Discussionmentioning
confidence: 60%
“…One important factor is heightened systemic vulnerability following release from detoxification programs and/or incarceration, [44][45][46] a time period in which the Bprotective factor^of abstinence can become a risk factor for fatal OD.…”
Section: Discussionmentioning
confidence: 99%